Panobinostat (LBH589): a potent pan-deacetylase inhibitor with promising activity against hematologic and solid tumors. (June 2009) - Prince, H Miles; Bishton, Mark J; Johnstone, Ricky W
The deacetylase inhibitors are a structurally diverse class of targeted antineoplastic agents that have demonstrated in vitro and in vivo preclinical activity in a wide range of malignancies. Based on this preclinical activity, several deacetylase inhibitors have undergone rapid clinical development in recent years. Among these, the deacetylase inhibitor panobinostat is one of the most widely studied, with extensive pharmacokinetic, pharmacodynamic and dose-finding data available across a wide variety of hematologic and solid tumors. Furthermore, panobinostat has demonstrated favorable clinical activity against various hematologic malignancies, most notably lymphomas and myeloid malignancies in Phase I and II studies. In this article, we discuss the preclinical data on panobinostat and emerging data from Phase I and II studies in cancer patients.